Possibilidades de avanços na concretização do direito fundamental à previdência social das pessoas com deficiência: distributividade, justiça social e liberalismo igualitário - Zacharias, Rodrigo (2022)
This work aims to advance the interpretation of the fundamental right to social security of the persons with disabilities (hereinafter referred to as PWD), based on the doctrine of constitutional law, especially from the perspective of social justice (art. 193 of the Federal Constitution) and the principle of distributivity (art. 194, single paragraph, III, of the FC), having as its main motto a contextualization from the perspective of egalitarian liberalism. This thesis initially intends to go beyond the traditional approaches given to controversies analyzed in judicial disputes, where - as observed by the candidate in his almost three decades of legal experience - it is customary to focus on the problem studied in the outlines of the principle of human dignity, the presumption of hyposufficiency of the litigant and the maxim “pro misero solution”. The word advancement, sometimes used in the plural, denotes the objective of obtaining favorable results for PWD in the interpretation of the law, of which some jurisprudence mistakes have been identified, chiefly concerning persons who are already born with significant impediments and face barriers throughout their professional lives, victims of currently insufficient social protection. An attempt was made to add to the traditional principles of social security law, the doctrine of which was built on constitutional law, with the contribution of the philosophy of law, specifically the one inspired by the egalitarian liberalism proposed by John Rawls, Amartya Sen, Martha Nussbaum and Ronald Dworkin. This thesis principally intends to base its conclusions on bibliographic research, but also on jurisprudential study, without neglecting the characteristics of field research obtained by the candidate in his activities as prosecutor and federal judge, thus merging inductive and deductive methods. Beginning with the heterogeneous, social and directing features of the Federal Constitution of 1988, through to the interpretation and implementation of its constitutional norms, the candidate concludes with an analysis of constitutional principles and essential characteristics of fundamental rights. Progress is made in the attempt to understand the rules of the social order, dealing with the primacy of work and the objective of social well-being. The principles of the distributivity of social security benefits and of social justice are highlighted, the former analyzed in the space reserved for social security, the latter dealt with in the chapter on egalitarian liberalism. As fundamental social rights, all the social security benefits, due to the PWD in reason of the disability or inability to work, were analyzed, with emphasis on the disability benefits. The main results are in the interpretation of the social right provided for the coverage of disease protection (article 201, I, of the Constitution, changed by Constitutional Amendment n.º 103/2019), impaired by historical legislative deficit; the identification of unsystematicity in the social protection of PWD's subsistence right, divided between welfare benefits and social security, proposing for legislative change; and finally in a new comprehension of the rules contained in articles 42, § 2 and 59, § 1, of Law nº 8.213/91, related to the PWD who are born with a disability or acquire them before turning sixteen years old, all based on interpretation conforming to the constitution, under the influence of the contractualist and distributive vision of egalitarian liberalism